George's secret key to the universe - Hawking, Lucy. (Simon & Schuster Audio, 2007)
Follows the adventures of a young boy and his neighbor friend as they travel through a computer portal into outer space, where they explore such mysteries as black holes and the origins of the universe, while trying to evade an evil scientist.